Pengaturan Pola Hidup Sehat Dengan Berpuasa Menurut Ajaran Islam - Zali, Muhammad; Zahra Salsabilla, Anggina; Syakir Haziq, Juan; Ramadhani Sitorus, Laila Atiyyah; Alifa Kamal, Nazla; Putri Cantika, Shafira (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
Fasting is abstaining from everything that breaks the fast, such as orgasm, stomach, and farji (genitals), from dawn to sunset, with a few conditions. This research aims to examine the regulation of a healthy lifestyle through fasting according to Islamic teachings, both from a spiritual and medical perspective. The method used is a literature study with a systematic search of primary sources such as the Qur'an, hadith, as well as scientific references and scholars related to fasting and health. The results of the study show that fasting not only has a ritual and spiritual dimension, but also provides great benefits for physical and mental health. In Islam, fasting is integrated as part of a healthy lifestyle that includes self-control, balanced food consumption, and increased spiritual awareness. In addition, fasting is scientifically proven to be able to help the body detoxify process, strengthen the immune system, and reduce the risk of chronic diseases such as diabetes and obesity. Islam comprehensively provides guidance for a healthy life that is balanced between physical and spiritual aspects, and emphasizes the importance of moderation and self-awareness in maintaining health. Thus, fasting in Islam plays a role as a form of worship that unites the dimensions of physical, spiritual, and social health.